“Hard” and “Soft” Privatization of Municipal Housing: A Case Study of the Warmia and Mazury Province in Poland - Muczyński Andrzej (Real Estate Management and Valuation, 2024)
Public housing privatization has changed the ownership and management patterns in Europe, leading to the emergence of many housing properties with a mixed (public-private) ownership structure. This study investigates the actual privatization degree of ownership and management in public-private housing condominiums (PPHCs) in Poland. In particular, the dependencies between these two types of housing privatization were identified. To achieve the aim of the study a multi-stage research methodology was applied, which was based on the triangulation of research methods such as questionnaire interviews, cluster analysis (using the agglomeration technique and Kohonen artificial neural network), and correlation analysis. Empirical research was conducted on the sample of the 30 largest municipalities from the Warmia and Mazury Province in Poland. The results showed different quantitative characterization and rather loose dependencies between the privatization of ownership and management of municipal housing in the sample of municipalities. This did not allow us to confirm the hypothesis that the privatization of ownership of municipal housing stock in PPHCs under study adequately drove the privatization of management in these properties. Therefore, the analysis of social, managerial, and institutional barriers to the privatization of property management services in PPHCs was recommended as a direction for further research.